2000
DOI: 10.1136/vr.147.12.319
|View full text |Cite
|
Sign up to set email alerts
|

Temporal aspects of the epidemic of bovine spongiform encephalopathy in Great Britain: holding.associated risk factors for the disease

Abstract: The objectives of this study were first to describe the pattern of the epidemic of bovine spongiform encephalopathy (BSE) in Great Britain in terms of the temporal change in the proportion of all cattle holdings that had experienced at least one confirmed case of BSE to June 30, 1997, and secondly to identify risk factors that influenced the date of onset of a holding's first confirmed BSE case. The analyses were based on the population of British cattle at risk, derived from agricultural census data collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 17 publications
6
46
0
Order By: Relevance
“…Secondly, no significant difference was found in the prevalence of Prionics positive cattle between cattle from dairy herds and those from beef suckler herds in the tested population [11]. This finding was in contradiction with British data since Wilesmith [18] found that the hazard ratio of being an affected herd was three times higher for dairy herds than for beef suckler herds, and 1.7 times higher for mixed herds, in agreement with previous studies [14,17].…”
Section: Introductionsupporting
confidence: 77%
“…Secondly, no significant difference was found in the prevalence of Prionics positive cattle between cattle from dairy herds and those from beef suckler herds in the tested population [11]. This finding was in contradiction with British data since Wilesmith [18] found that the hazard ratio of being an affected herd was three times higher for dairy herds than for beef suckler herds, and 1.7 times higher for mixed herds, in agreement with previous studies [14,17].…”
Section: Introductionsupporting
confidence: 77%
“…So, in order to define a study sample in which cases and controls have been submitted to a global comparable level of risk, they were matched on their birth cohort. The production type of cattle, dairy or beef, was also considered as a potential confounding factor [13,23]. Since the farmer practices concerning the cattle feeding were related 512 N. Jarrige et al to the production type, it was decided not to pair cases and controls on this factor to avoid a possible overmatching bias but to consider it as a potential confounder in the model.…”
Section: Discussionmentioning
confidence: 99%
“…This tends to prove that the effect of the production type was due to the factors related to feedstuff consumption. Concerning the herd size, it was introduced in the final model as an offset, considering that large herds have a statistically greater chance to have a case than small ones [23] and that farmer practices also depend on the herd size. The process of inclusion of the bovines in the sample study was made so as to know the reason of each exclusion.…”
Section: Discussionmentioning
confidence: 99%
“…It helped to keep the study as powerful as possible. However, we made an adjustment for the production type of cattle which is highly related to the BSE risk [15,26], first because the culling rates differ between the two types, second because we cannot exclude that the BSE incubation period varies between dairy and beef cows. Another modelling approach might have been to build a single model with the entire slaughtered population and incorporating interaction variables between the year of test of birth cohorts to account for the postulate that the effect of the year of test depended on the birth cohorts being tested; comparing the odds of being a cow of a given birth cohort slaughtered in 2001 to those of a cow of the following birth cohort slaughtered in 2002 would have given the estimates of the risk increase/ reduction between cohorts.…”
Section: Methodsmentioning
confidence: 99%